Perspectives and Reflections on Media, Gender, Children and Culture in the Digital Age - Timothy Ekeledirichukwu Onyejelem; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2025)
This paper explores the dynamic intersections of media, gender, children, and culture in the context of the digital media, where technological advancements have reshaped how identities are constructed, communicated, and contested. Drawing on interdisciplinary perspectives, the paper examines how digital media platforms influence the socialization of children, the reinforcement or disruption of gender norms, and the negotiation of cultural values. The paper reflects on how children are no longer passive recipients of media messages but active agents who engage with, interpret, and even produce content, often navigating complex terrains of gendered and cultural representation. It also considers how globalized digital media flows intersect with local cultural contexts, affecting how children perceive themselves and others. The paper argues that many feminists believe that media by its power and its agenda-setting role, which include giving prominence to people and events, have portrayed women in the most unfavorable terms whether as key players in the media industry or as recipients of media content. The power of the media extends not only to what is covered, but also what is omitted. Women have been omitted by the media despite their upliftment in the last half of a century from mothers and wives to professionals with expertise in many fields of human endeavour. The paper further interrogates the implications of algorithmic content delivery, media literacy gaps, and digital inequalities. Through critical reflections and analysis, the paper advocates for inclusive media policies and culturally sensitive media literacy approaches that recognize children’s agency while addressing structural constraints.